Human capital formation and global warming mitigation: evidence from an integrated assessment model - Carlo Carraro; Enrica de Cian; Massimo Tavoni (Center for Economic Studies and ifo Institute (CESifo), 2009)
Based on recent empirical evidence, this paper includes human capital and knowledge in an integrated assessment model and it assesses the interplay between innovation, human capital, climate change, and education policies. Results indicate that climate policy stimulates a dedicated form of energy-knowledge without reducing generic R&D investments. Since advancements in labour productivity have a negative impact on the environment because labour is assumed to be complement to energy, climate policy reduces education investments, on which human capital is built. However, a policy mix combining climate and education targets shows that education and climate goals can be coupled incurring in small additional economic penalties.
Keywords: Q43; O33; O41; 330; climate policy; innovation; human capital